Swing JIB rack stacker crane - M. S. Korytov; A. E. Bezrodina (Вестник СибАДИ, 2022)
Introduction. Rack stacker cranes are the main hoisting and transport machine for maintenance of multi-level rack warehouses. The efficiency and profitability of the warehouse depends on their efficiency. The traditional design of a rack stacker crane includes a trolley that moves along the rails on the floor of a warehouse, a column mounted vertically on the trolley, along which a carriage with a load gripping device and a load rises. The disadvantages of the traditional crane design are the relatively large mass of the trolley, the need to move it along with the column in a horizontal direction when moving around the warehouse, the relatively high energy consumption and the need to strengthen the floor of the warehouse. The crane rail tracks on the floor of the warehouse must be cleared of objects falling from above, which is associated with stopping the operation of the crane and reducing productivity.Materials and Methods. The design of a stacker crane is related to the shape of its working space. In order to improve the stacker crane, its design was developed on the basis of a jib with a counterweight, which does not require rail crane tracks. The crane of the proposed design is capable of storage in the hangars of a semicircular shape. For two warehouses: traditional rectangular and semicircular shapes, a comparative analysis of the sums of geometric distances was performed when the load gripping device moved from the loading point to randomly selected target cells. As a comparison criterion, the sum of the Cartesian distances of the load gripping device movements between the warehouse loading point and the target points, randomly selected according to the law of uniform distribution, was used. Three types of crane operation cycles were studied – simple single, double and mixed.Results. Comparative diagrams of criterion values are given. It has been established that for all types of cycles studied, to the greatest extent when working on a single cycle, the use of a crane of the proposed design with the same storage capacity significantly reduces the total geometric distance that the load gripping device must pass.Discussion and conclusions. Reducing the sum of the geometric distances of movement of the load handling device of the new crane allows to conclude that the time spent on the movements that determine the productivity of the work performed by the crane, as well as the energy costs associated with them, can be significantly reduced. Reducing energy costs is possible by replacing the translational movement of a massive undercarriage with the rotational movement of a balanced jib of a relatively small mass at the crane of the proposed design. Time is not wasted on regular cleaning of the crane tracks, associated with stopping the crane. The number of friction pairs in the proposed design of the crane is reduced compared with the traditional one.